The impact of impulsivity and compulsivity on error processing in different motivational contexts. - Overmeyer, Rebecca; Endrass, Tanja (Cognitive, Affective & Behavioral Neuroscience, 2025)
Neural correlates of performance monitoring, specifically the error-related negativity (ERN), are not only sensitive to motivation, but also altered in mental disorders marked by high levels of impulsivity and compulsivity. We explored the relationship between the ERN and individual differences in impulsivity and compulsivity. A total of 221 participants were recruited along the dimensions of impulsivity and compulsivity, and they performed a flanker task with a potential gain and a loss avoidance motivational context to assess error-related brain activity. We examined the ERN and theta power. Single trial regression was employed to analyze effects of motivational context and the relation to impulsivity and compulsivity. High impulsivity and compulsivity predicted higher ERN amplitudes within the gain context, but not the loss context. The interaction between both resulted in ERN amplitudes in the gain context being largest when impulsivity was high and compulsivity was low, and smallest when both were low. The ERN amplitude difference between gain and loss trials was highest if both impulsivity and compulsivity were low. Results indicate that both impulsivity and compulsivity are associated with larger ERN in the gain context, probably indicating higher subjective error significance. Both show a reduced modulation of the ERN with motivational context suggesting deficits in adaptive regulation of performance monitoring. Exploring transdiagnostic markers and their interactions could provide valuable insights into unraveling the complex dynamics that arise when examining the neural correlates of performance monitoring within the context of motivational effects.